Sequencing Multimegabase-Template DNA with BigDye Terminator Chemistry - Heiner, Cheryl R.; Hunkapiller, Kathryn L.; Chen, Shiaw-Min; Glass, John I.; Chen, Ellson Y.

(untitled) (Genome Research, 1998)
Using the recently introduced BigDye™ terminators, large-template DNA can be directly sequenced with custom primers on automated instruments. Cycle sequencing conditions are presented to sequence DNA samples isolated from a number of microbial genomes including 750-kb Ureaplasma urealyticum, 1.2-MbMycoplasma fermentans, 2.3-Mb Streptococcus pneumoniae, and 4.6-Mb Escherichia coli. Average read lengths of >700 bp from unique primer annealing sites are often sufficient to fill final gaps in microbial genome sequencing projects without additional manipulations of template DNA. The technique can also be applied to sequence-targeted regions, thereby bypassing tedious subcloning steps.